Trust and credibility of urban youth on online news media - Sharon, Wilson; Pauline, Leong; Carmen, Nge; Ngerng, Miang Hong (Universiti Kebangsaan Malaysia, 2011)
When the Internet was introduced, there were comparatively few websites, especially news websites. Today, new media technology’s drastic developments in the communications field have had a big impact on society at large. The development and larger availability of information and activities seem to offer people the opportunity of quick access, and systematically providing, in seconds, what would have previously taken months of perusing newspaper stacks of microfilm rolls (Deacon, 2007). These features supersede the more traditional print medium in terms of delivering news with immediacy and impact, and act as a powerful lure that continually draws readers. This paper investigates online consumer behaviour with regards to student perceptions of the trust and credibility of online news. From a survey of 1,000 students of institutions of higher education in the Klang Valley, findings reveal that youth still rely on traditional media to obtain news. However, traditional media fails to provide sufficient information for youth so they resort to getting additional information from alternative news websites. Nevertheless, their level of trust in alternative news websites is based on how accurately these sites reflect the current scenario. Findings also reveal that students believe alternative news websites present different viewpoints, are more critical, have more in-depth analysis and are relatively free from interference.All these factors seemingly contribute to youth’s trust of the alternative news websites they read. What is interesting is the fact that the trust extends to alternative online news sources but excludes blogs and the findings clearly show that the youth are not weaned off of traditional media.